2016
DOI: 10.1016/j.jand.2015.06.383
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Perception: Associations with Weight Control Goals, Attempts, and Practices among Chinese Female College Students

Abstract: Background Concurrent with the dramatic cultural and economic shifts occurring as Mainland China becomes increasingly “Westernized,” the weight perceptions, ideal body weight, and weight management goals and practices of Chinese females have also undergone significant changes. Objective To investigate relationships between overweight status, weight perception patterns, and weight management goals and practices in Chinese female college students. Design/Participants/Setting A cross-sectional analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…In addition, although approximately 13% of the participants were either overweight or obese, 50% considered themselves as being slightly fat or very fat. A previous study involving Chinese female college students reported similar results; nearly 17% of the women in that study were overweight or obese but 51% perceived themselves as being too fat [ 2 ]. Additionally, this study reported a relatively lower proportion of Chinese students (20.2%) who used extreme weight control methods (e.g., inducing vomiting, using laxatives or diuretics, and taking diet pills) among participants making an effort to lose or maintain their weight [ 2 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In addition, although approximately 13% of the participants were either overweight or obese, 50% considered themselves as being slightly fat or very fat. A previous study involving Chinese female college students reported similar results; nearly 17% of the women in that study were overweight or obese but 51% perceived themselves as being too fat [ 2 ]. Additionally, this study reported a relatively lower proportion of Chinese students (20.2%) who used extreme weight control methods (e.g., inducing vomiting, using laxatives or diuretics, and taking diet pills) among participants making an effort to lose or maintain their weight [ 2 ].…”
Section: Discussionsupporting
confidence: 59%
“…A previous study involving Chinese female college students reported similar results; nearly 17% of the women in that study were overweight or obese but 51% perceived themselves as being too fat [ 2 ]. Additionally, this study reported a relatively lower proportion of Chinese students (20.2%) who used extreme weight control methods (e.g., inducing vomiting, using laxatives or diuretics, and taking diet pills) among participants making an effort to lose or maintain their weight [ 2 ]. Considering the adverse side effects and widespread practice of unhealthy weight control methods among the students in the present study, educating them on healthy weight control methods is an urgent requirement.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The discrepancy between actual weight and subjective weight ideals can be quantified with questions that assess actual versus perceived or desired weight (10,(12)(13)(14)(15), Stunkard silhouettes (16)(17)(18), or a simple calculation. Existing research on the discrepancy between actual and ideal weight has mostly been conducted in special populations, such as college students, migrants, and physically active individuals (12)(13)(14)(15)37). Based on these studies, sociocultural changes and Western media exposure may increase negative body image (14,15), and the discrepancy between actual and ideal body image can be associated with maladaptive eating and exercise patterns (13).…”
Section: Introductionmentioning
confidence: 99%
“…The university stage is the stage in which ideas and behaviors are formed and developed stably and also the critical period in which diet and wholesome habits are formed. College students generally have a good knowledge of the receiving ability, but the survey finds that the overall cognitive health literacy of college students is relatively low, especially in weight cognition, many college students can't distinguish whether he really fat, think oneself fat college students than the students the actual BMI exceeds bid [1], more than 60% college students cannot rationally judge their own weight, in addition, 78% of participants lost weight for the purpose of being more beautiful rather than healthy [2][3][4][5]. As the main force in the future social development, the health status of college students is attracting mounting number of attention.…”
Section: Introductionmentioning
confidence: 99%